Pengaruh Perencanaan Pajak dan Beban Pajak Tangguhan Terhadap Manajemen Laba - Lucy Devitasari (Jurnal Pajak dan Bisnis, 2022)
The purpose of this study was to examine the effect of tax planning and deferred tax expense on earnings management. The object of this research uses 18 conventional bank companies listed on the Indonesia Stock Exchange (IDX) that have met the criteria and completeness of the data. The sampling technique used was the purposive sampling method. The data used in this research is secondary data. Using the financial statements of conventional banks listed on the Indonesia Stock Exchange during the 2017-2019 period. The research method uses linear regression analysis. The results showed that tax planning had a significant negative effect and deferred tax expense had a significant positive effect on earnings management